A quantitative atom probe study of the Nb excess at prior austenite grain boundaries in a Nb microalloyed strip-cast steel - Felfer, Peter; Killmore, Chris R.; Williams, Jim G.; Carpenter, Kristin R.; Ringer, Simon P.; Cairney, Julie M. (Acta Materialia, 2012)
Most modern HSLA steels rely on the effect of Nb in steels to achieve the properties desired for a specific application. While the role of Nb in forming precipitates has been well characterized, its role in a solid solution is less well understood due to the difficulty of obtaining quantitative experimental data. In the current work, site-specific atom probe tomography was used to quantify the amount of Nb present at prior austenite grain boundaries in a commercial strip-cast steel, produced via the Castrip process. This was compared to the amount of Nb found at ferrite-ferrite grain boundaries that had formed during the transformation from austenite to ferrite. With the interfacial excess Nb measured, thermodynamic calculations were carried out and compared to the change in transformation temperature obtained by dilatometry, with reference to a comparable Nb free, strip-cast steel. © 2012 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserve
Keywords: Atom probe tomography; Bainitic steel; Grain boundary segregation; Nucleation of phase transformations; Strip-casting